Anxiety and COVID-19: A study of online content readability. Issue 2 (3rd April 2021) - Seidel, Erica J.; Hillyer, Grace C.; Basch, Corey H.
Abstract: The uncertain and unprecedented nature of the COVID-19 pandemic is anxiety-provoking and some people are seeking information about this anxiety online. The purpose of this study was to assess the readability levels of online articles related to anxiety and COVID-19. The first 50 English language URLs to appear in a Google search in July 2020 were assessed for readability using Readable.io. A five-measure panel consisting of the Flesch–Kincaid Grade Level (FKGL), Gunning Fog Index, Coleman–Liau Index (CLI), the Simple Measure of Gobbledygook (SMOG) Grade Level, and Flesch–Kincaid Reading Ease (FRE) was used, and grade level scores were recoded as easy, average, and difficult readability. Websites were grouped as commercial vs. noncommercial sources bases on the URL. Of the 50 articles evaluated, the majority were found to be written at a difficult (>10th grade) reading level with four of the five measures employed which is well above the 7–8th grade reading level abilities of most Americans. Given the importance of access to mental health information during the pandemic, it is crucial that the resources available to the general public are written at a reading level that is comprehensible to ensure they are understood.